Longitudinal relationships between daily activities, depressive symptoms, anxiety, and suicidality during the COVID-19 pandemic: a three-wave cross-lagged study - Choi, Juhee; Son, Gaeun; Choi, Kee-Hong (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic has caused significant unprecedented changes in lives. In particular, core daily activities, such as sleep, diet, physical activity, education, and social activities have significantly changed. Restrictions on daily activities are associated with the deterioration of mental health. However, few studies have comprehensively explored the relationship between daily activities and mental health during the COVID-19 pandemic, and longitudinal studies of these relationships are lacking. Therefore, this study examined the dynamic interaction between core daily activities and mental health during the COVID-19 pandemic.MethodsAn online survey was conducted with 586 adults (age: M = 46.80, SD = 12.515) in three waves: September 2020, December 2020, and April 2021. Depressive symptoms, anxiety, and suicidality were assessed using Mental Health Screening Tool. Daily activities were assessed using Core Life Activities Inventory. Autoregressive and cross-lagged effects were investigated using a cross-lagged panel analysis.ResultsReduced daily activities contributed to increased depression, anxiety, and suicidality, which, in turn, resulted in further decreases in daily activities in subsequent waves. These autoregressive and reciprocal effects persisted for 7 months during the pandemic. Among core daily activities, sleep quality, physical activity, and social activities had reciprocal relationships with depression. Moreover, only social activities showed a reciprocal relationship with anxiety and suicidality.ConclusionThese findings highlight the complex relationship between core daily activities and mental health and provide valuable insights for targeted therapeutic strategies. Implementing timely and effective interventions to maintain and enhance key activities, particularly social engagement, is crucial for alleviating negative mood symptoms. Clinical support and promotion of these essential daily activities are necessary to improve mental health outcomes.